Correlation of the expressions of IGF1R‐RACK1‐STAT3 and Bcl‐xl in nasopharyngeal carcinoma with the clinicopathological features and prognosis of nasopharyngeal carcinoma. Issue 2 (18th September 2017) - Wang, Shan; Shen, Min; Wen, Xin; Han, Xin‐Rui; Wang, Yong‐Jian; Fan, Shao‐Hua; Zhuang, Juan; Zhang, Zi‐Feng; Shan, Qun; Li, Meng‐Qiu; Hu, Bin; Sun, Chun‐Hui; et al.
Abstract: The aim of this study was to investigate the correlation of expression of IGF1R‐RACK1‐STAT3 and Bcl‐xl in nasopharyngeal carcinoma (NPC) with the clinicopathological features and the prognosis of NPC. Our study selected 215 NPC tissues and 178 chronic nasopharyngitis tissues (control group). Positive expression rates of IGF1R, RACK1, STAT3, and Bcl‐xl were tested by immunohistochemical method, and expression of IGF1R, RACK1, STAT3, Bcl‐xl, Bcl‐2, and Bax by western blotting. Correlation of IGF1R, RACK1, STAT3, and Bcl‐xl with the clinicopathological features of NPC was analyzed. The correlation among those four expression was analyzed by Spearman. The survival of NPC and independent factors of prognosis were tested by Kaplan‐Meier and COX proportional hazards model respectively. The NPC group had higher positive expression rates of IGF1R, RACK1, STAT3, and Bcl‐xl, and elevated expression of IGF1R, RACK1, STAT3, Bcl‐xl, Bcl‐2, and Bax. The lymph node metastasis (LNM) group had higher positive expression rates of IGF1R and RACK1 when compared with the non‐LNM group. Patients with stage III and IV had higher positive expression rates of IGF1R, RACK1, STAT3, and Bcl‐xl. There was positive correlation between expression of IGF1R and RACK1, STAT3. Such correlation was found between RACK1 and STAT3. Patients with negative expression of IGF1R, RACK1, STAT3, and Bcl‐xl had higher survival rates. The risky factors of poor prognosis of NPC were positive expression of IGF1R, RACK1, STAT3 and Bcl‐xl, and LNM. IGF1R‐RACK1‐STAT3 and Bcl‐xl expression correlated with the clinicopathological features and poor prognosis of NPC. Abstract : The risky factors of poor prognosis of NPC were positive expression of IGF1R, RACK1, STAT3 and Bcl‐xl and LNM. IGF1R‐RACK1‐STAT3 and Bcl‐xl expression correlated with the clinicopathological features and poor prognosis of NPC.